2013
DOI: 10.4028/www.scientific.net/kem.549.180
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Pyramid Steel Sheet Formed by Single Point Incremental Forming Using Solid-Shell Finite Elements

Abstract: Single Point Incremental Forming (SPIF) is an interesting manufacturing process due to its dieless nature and its increased formability compared to conventional forming processes. Nevertheless, the process suffers from large geometric deviations when compared to the original CAD profile. One particular example arises when analyzing a truncated two-slope pyramid [. In this paper, a finite element simulation of this geometry is carried out using a newly implemented solid-shell element [, which is based on the En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This fact is also supported by previous simulations using the solid-shell element formulation (e.g. Duchêne et al, 2013;Sena et al, 2013). Localization is nonetheless a different aspect of the deformation.…”
Section: Analysis Of Fracture Prediction By the Gurson Modelsupporting
confidence: 73%
See 1 more Smart Citation
“…This fact is also supported by previous simulations using the solid-shell element formulation (e.g. Duchêne et al, 2013;Sena et al, 2013). Localization is nonetheless a different aspect of the deformation.…”
Section: Analysis Of Fracture Prediction By the Gurson Modelsupporting
confidence: 73%
“…Guzmán et al (2012a) showed using the SSH3D solid-shell element for a line test simulation, that the element flexibility modified by EAS modes can severely decrease the force level. This was later confirmed by a pyramid test simulation by Duchêne et al (2013). Potential reasons for high forces were studied by Sena et al (2016) (boundary conditions, missing blankholder force modeling, friction coefficient, hardening modeling choice, element stiffness, etc.).…”
Section: Fe Simulationmentioning
confidence: 72%
“…The hardening type adopted is a mixed one, with an isotropic constitutive model. The kinematic part of the hardening is introduced by a back-stress tensor described by non-linear Armstrong-Fredrick model (Duchêne et al, 2013). The plastic domain is described by a von Mises yield surface and the isotropic hardening behaviour is defined by means of a Swift's law.…”
Section: Two-slope Pyramid Numerical Validationmentioning
confidence: 99%
“…The experimental tool path points were given in order to use it in the numerical simulations. These SPIF experiments as well as the shape measurements were performed by the team at KU Leuven (Duchêne et al, 2013) The shape analysis is divided in four sections (A, B, C, D), in order to analyse them separately in the middle section of the mesh model (see Figure 6), to avoid the influence of Boundary Conditions (BC). The material behaviour is elastically described by E = 142800 MPa and ν = 0.33.…”
Section: Two-slope Pyramid Numerical Validationmentioning
confidence: 99%
See 1 more Smart Citation